Production of Infectious Dengue Virus in Aedes aegypti Is Dependent on the Ubiquitin Proteasome Pathway. - Milly M Choy; October M Sessions; Duane J Gubler; Eng Eong Ooi (Public Library of Science (PLoS), 2015)
Dengue virus (DENV) relies on host factors to complete its life cycle in its mosquito host for subsequent transmission to humans. DENV first establishes infection in the midgut of Aedes aegypti and spreads to various mosquito organs for lifelong infection. Curiously, studies have shown that infectious DENV titers peak and decrease thereafter in the midgut despite relatively stable viral genome levels. However, the mechanisms that regulate this decoupling of infectious virion production from viral RNA replication have never been determined. We show here that the ubiquitin proteasome pathway (UPP) plays an important role in regulating infectious DENV production. Using RNA interference studies, we show in vivo that knockdown of selected UPP components reduced infectious virus production without altering viral RNA replication in the midgut. Furthermore, this decoupling effect could also be observed after RNAi knockdown in the head/thorax of the mosquito, which otherwise showed direct correlation between infectious DENV titer and viral RNA levels. The dependence on the UPP for successful DENV production is further reinforced by the observed up-regulation of key UPP molecules upon DENV infection that overcome the relatively low expression of these genes after a blood meal. Collectively, our findings indicate an important role for the UPP in regulating DENV production in the mosquito vector.